Mapping the Nexus of Geopolitical Tension and Investment in Emerging Markets : A Bibliometric and Thematic Analysis - Dewi Ratih (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Geopolitical tensions have evolved from peripheral risks to central drivers of global capital flows, disproportionately affecting Emerging Markets (EMs). This study provides a comprehensive bibliometric mapping of the academic landscape linking geopolitical dynamics, international finance, and investment in EMs. This study uses a dataset of 1,039 documents extracted from high-impact databases to analyze performance and conduct science mapping with R-Bibliometrix. The analysis covers publication trends, citation structures, and conceptual evolution over the last century, with a focus on the surge in literature post-2018. Results indicate an exponential growth in scientific production, peaking in 2024. The thematic structure reveals a shift from traditional debt crisis narratives (1990s) to contemporary concerns regarding sanctions, protectionism, and trade policy (2020s). Network analysis identifies three distinct clusters: (1) International finance and market mechanisms, (2) Political economy and development in the Global South, and (3) Institutional governance (IMF/World Bank). This paper bridges the gap between political science and financial economics by visualizing how international finance serves as the dominant anchor connecting developed economies (the USA and the UK) with key emerging markets (China and Indonesia) amid rising global fragmentation.